Preparation and Performance of Silica Membranes on alpha-Alumina Flat Disk for Bio-CNG (CH4/CO2) Purification - Putri, Jesika Kirana; Ramadhanu Dirja; Suprihatin; Hens Saputra; Ade Andini; Arfiana (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
This study focuses on the synthesis and performance evaluation of silica membranes supported on ?-–alumina flat disks for bio–CNG (CO2/CH4) purification. The membranes were fabricated via a sol–gel method using tetraethyl orthosilicate (TEOS) as the silica precursor and cetyltrimethylammonium bromide (CTAB) as the templating agent. CTAB concentrations were varied from 0.01 to 0.09 M, while drying temperatures ranged from 80 to 120 °C. Characterisation through SEM–EDX, XRD, and gas permeation tests revealed that an increase in CTAB concentration produced a more uniform pore structure and enhanced CH4 flux. However, excessive CTAB led to over–templating, resulting in microcracks. The optimal membrane was obtained at 0.05 M CTAB and a drying temperature of 105 °C, yielding a separation factor (?- = 2.14) with stable structural integrity. Gas transport was dominated by Knudsen diffusion, favouring CH4 over CO2, with an experimental CH2/CO4 selectivity (?- = 3.21) exceeding the theoretical Knudsen value (1.66). This indicates that, in addition to Knudsen flow, microstructural factors such as pore interconnectivity and partial defects contributed to CH4 transport through the silica membrane. These findings indicate that silica membranes synthesised under optimised sol–gel conditions exhibit strong potential for efficient bio–CNG upgrading, supporting renewable, low–carbon energy applications. Contribution to Sustainable Development Goals (SDGs):SDG 7: Affordable and Clean EnergySDG 9: Industry, Innovation, and InfrastructureSDG 13: Climate Action